Формування ланцюга поставок на основі ідентифікації споживчих потреб - Якимишин, Лілія Ярославівна (Видавництво Львівської політехніки, 2017)
Ідентифіковано найбільш суттєві потреби споживачів товарів повсякденного попиту, які має задовольняти конкретний ланцюг. Проаналізовано особливості товарів повсякденного попиту, що дало змогу ідентифікувати їх типовий перелік з погляду вітчизняного споживача. Виокремлено дві великі групи товарів повсякденного попиту, які покладено в основу досліджуваного ланцюга поставок: продукти харчування і напої; нехарчові продукти. Виявлено найбільш суттєві характеристики товарів повсякденного попиту з позиції виробника, ринку та інших його учасників. Встановлено наявність серйозних бар’єрів в Україні розвитку ланцюгів поставок, що є стимулом для перегляду підприємствами своїх бізнес-процесів і пошуку шляхів підвищення їх ефективності.

The most essential consumer needs of every day goods meeting the demands of specific chain are identified. It is determined that from the point of view on supply chains control goods classification according to the character of their final use is of great importance. It gives us an opportunity to identify the needs of end-consumers, their preferences and customs, which in its turn specify approaches to the promotion, production and supply of such products in the chains and developing effective relationship between participants as well. Carried our investigation of every day goods peculiarities made it possible to identify their typical list from the point of view of domestic consumer. Two large groups of every day goods which form the basis of the investigated supply chain: food products and drinks, nonfood products are distinguished. The most essential characteristics of every day goods from the points of view of producer, market and their participants are defined. The main distinctive features of the market selling every day goods are identified. They are: seasonality, high competition, dynamics, constant struggle for leadership. It was determined that the shift of consumer needs to cheaper every day goods produced in Ukraine as the result of the decrease of the population purchase power is the main tendency. Every day goods peculiarities from the points of view of manufactures and distributors are defined. As the result the reasons for the concepts of such products promotion, production and supply in supply chains as well as logistic aspects of these processes control were given. Comparison of these criteria according to the perspective of manufactures and distributors led to the following conclusions: financial results of both manufactures and distributors activity to a large extend is rather stable and high; two main sales peculiarities are the speed of assortment renewal which is high for distributors taking into account their dependence on consumer needs changes and low for manufacturers who tend first and foremost to implement scale effect for cost saving; the role of marketing in products realization which is insignificant for manufacturers but significant for distribution; from the point of view of logistics it is important competence for both market players, the main difference is in supply volume – for manufacturers they are large products lots while distributors tend to order small ones. Summarized market characteristics of every day goods and its participants depicts comparison of peculiarities in the whole market of the investigated products group with characteristic features of manufacturing companies and distributors which is the useful tool in the guideline selection for actual strategic and operative decisions choice for every day goods supply chains. The existence of serious barriers in Ukraine concerning supply chains development is determined. It motivates revision of business-processes by enterprises and search of the ways of the increase of their effectiveness.
Formation of supply chain on the basis of consumer needs identification
Keywords: ланцюг поставок; товари повсякденного попиту; потреби споживачів; ринок товарів повсякденного попиту; supply chain; everyday goods; consumer needs; every day goods market; 658.7; 001.895